Weight Loss: How Does It Fit in With Liposuction?. (October 2020) - Davis, William; Lawrence, Naomi
Abstract : BACKGROUND: Weight loss is traditionally viewed as straightforward counting of calories in and calories out, with little regard to the role of the adipocytes tasked with storing said calories. However, the body executes a complex compensatory response to any intervention that depletes its energy stores. Here, the authors discuss the methods used to attain weight loss, the body's response to this weight loss, and the difficulties in maintaining weight loss. Furthermore, the authors provide an overview of the literature on the physiological effects of liposuction. OBJECTIVE: To describe the role of adipose tissue in energy homeostasis, methods of weight loss, weight regain, and the effect of liposuction on endocrine signaling. METHODS: The authors conducted a narrative review of representative studies. CONCLUSION: A variety of strategies for weight loss exist, and optimizing one's weight status may in turn optimize the aesthetic outcomes of liposuction. This is most apparent in the preferential reaccumulation of fat in certain areas after liposuction and the ability to avoid this with a negative energy balance.